The characteristics of the expression of heat shock proteins and COX-2 in the liver of hamsters infected with Clonorchis sinensis, and the change of endocrine hormones and cytokines - Choi, WonHyung; Chu, JongPhil (Folia parasitologica, 2012)
The liver fluke Clonorchis sinensis (Digenea) is a high-risk parasite that causes serious diseases such as cirrhosis, carcinogenic liver damage and clonorchiasis in East Asia. This study was conducted to evaluate the relationship between stress/endocrine hormones and inflammation induced by infection as well as the expression of heat shock proteins (hsp-27, hsp-90), cox-2 and cytokines in the livers of hamsters infected with C. sinensis. The average body weight of infected hamsters decreased up to 25% compared with that of the control group, and bile duct hyperplasia with inflammation, liver fibrosis and hepatic necrosis were observed in C. sinensis-infected livers. The expression of hsp-27, hsp-90, and cox-2 was significantly increased in the livers of C. sinensis-infected hamsters compared with the control group. Moreover, the expression levels of inflammatory cytokines (IL-1beta, IL-2, TGF-beta2 and IFN-alpha1) were markedly increased in the livers of the infected group compared with those of the control group. Consistently, plasma IL-3 and IL-6 levels gradually increased during the infection period, and the concentration levels of testosterone, luteinizing hormone (LH), follicle-stimulating hormone (FSH), corticosterone, and adrenocorticotropic hormone (ACTH) in C. sinensis-infected hamsters increased over 25%, compared with those of the uninfected normal group. These results demonstrate that C. sinensis infection may increase the expression of hsp27, hsp90 and cox-2 as well as it may cause periductal fibrosis, chronic inflammation and hepatic necrosis in the liver. Furthermore, the results indicate that C. sinensis infection induces not only stress-induced hormone imbalance but also the sustained secretion of inflammatory cytokines through chronic stress/stimuli.
Keywords: Liver; Animals; Clonorchis sinensis; křečci praví; Cytokines; Clonorchiasis; játra; Cyclooxygenase 2; Heat-Shock Proteins; cytokiny; Hormones; klonorchióza; regulace genové exprese; cyklooxygenasa 2; hormony; Gene Expression Regulation; zvířata; proteiny teplotního šoku; Cricetinae